Molecular prevalence and subtype distribution of Blastocystis sp. in Asia and in Australia - Sara Nemati; Mohammad Reza Zali; Paul Johnson; Hamed Mirjalali; Panagiotis Karanis (IWA Publishing, 2021)
Blastocystis is a prevalent protozoan parasite reported in humans, animals, and environmental samples. Over the past decade, numerous studies have investigated the prevalence and subtype distribution of Blastocystis sp. alongside with its genetic and biochemical features. However, studies on subtype distribution of this protozoan in humans, animals, and environmental samples represent the potential transmission routes. In this review, we evaluated studies performed in Asian countries and in Australia to provide an overview of environmental factors on the prevalence and subtype distribution of Blastocystis sp. among humans, animals, and the environment. HIGHLIGHTS Blastocystis sp. is a prevalent protozoan reported in humans, animals, and the environment.; Subtype distribution represents the potential transmission routes.; The prevalence and the distribution pattern of subtypes vary from the east to the west countries in Asia.;